Indonesia PENERAPAN PENGENDALIAN BUDAYA DALAM MENGATASI DISONANSI KOGNITIF - Tjandra, Edi (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2024)
Cognitive dissonance in decision-making can lead to future problems. This research aims to explore how proper cultural control can prevent or eliminate cognitive dissonance. Effective cultural control, through continuous training, fair reward programs, and consistent enforcement of discipline, helps align employee actions with organizational values. With effective communication and management demonstrating integrity and professionalism, a supportive and motivating work environment can be created. This helps reduce the misalignment between employees' beliefs and actions, improving performance, and ensuring the achievement of organizational goals more efficiently and harmoniously. Keywords: Cognitive Dissonance, Cultural Control, Decision-Making.